1996
DOI: 10.1007/bf03402210
|View full text |Cite
|
Sign up to set email alerts
|

The Immunoregulatory Mediator Macrophage Migration Inhibitory Factor (MIF) Catalyzes a Tautomerization Reaction

Abstract: Background: Recent studies of melanin biosynthesis have uncovered an unusual enzymatic activity which converts the non-naturally occurring D-isomer of 2-carboxy-2, 3-dihydroindole-5,6-quinone (dopachrome) into 5,6-dihydroxyindole-2-carboxylic acid (DHICA). The aim of the present investigation was to isolate and characterize the enzyme catalyzing this tautomerization reaction. Materials and Methods: After we performed a tissue survey of D-dopachrome tautomerase activity, 10 bovine lenses were homogenized and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
292
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(298 citation statements)
references
References 26 publications
4
292
0
2
Order By: Relevance
“…The crystal structure shows that the active form is a 37.5 kDa homotrimer with new protein folds (Sun et al, 1996b). MIF has Pro-Pro dependent tautomerase activity and CALC dependent oxidoreductase activity (Rosengren et al, 1996;Thiele & Bernhagen, 2005). The tautomerase activity allows the MIF to catalyze D-dopachrome or L-dopachrome to its indole derivatives (Rosengren et al, 1996).…”
Section: Genetics and Structure Of Mifmentioning
confidence: 99%
“…The crystal structure shows that the active form is a 37.5 kDa homotrimer with new protein folds (Sun et al, 1996b). MIF has Pro-Pro dependent tautomerase activity and CALC dependent oxidoreductase activity (Rosengren et al, 1996;Thiele & Bernhagen, 2005). The tautomerase activity allows the MIF to catalyze D-dopachrome or L-dopachrome to its indole derivatives (Rosengren et al, 1996).…”
Section: Genetics and Structure Of Mifmentioning
confidence: 99%
“…MIF tautomerase/isomerase activity relies on Pro-1 that promotes enolization and ketonization (10,43). Because its natural ligand is unknown, MIF enzymatic properties have been described in detail using molecular models as substrates (44).…”
Section: Mif Peptidementioning
confidence: 99%
“…First, MIF can function as a pro-inflammatory protein, as assessed by its inhibitory effect on dexamethasone-mediated TNF-␣ production (2) and its ability to sustain CD3-mediated T cell proliferation (8) and pro-inflammatory cytokine secretion (9). MIF also possesses enzymatic activities as a tautomerase/isomerase (10) and thiol oxidoreductase (11). However, the natural substrates for MIF catalytic activity are unknown even though its enzymatic activity has been characterized in detail using insulin and L-DOPA as models (11,12).…”
mentioning
confidence: 99%
“…On the other hand, although MIF was recently reported to catalyze the tautomerization of 2-carboxy-2,3-dihydroindole-5,6-quinone (o-dopachrome) to 5,6-dihidroxyindole-2-carboxylic acid (DHICA) [8], nothing is known about its active site. MIF does have a pocket in a similar region close to the N-terminal Pro residue.…”
Section: Pro Cys Ala Leu Cys Ser Leu Ais Ser Ile Gly Lys Ile Gly Gly mentioning
confidence: 99%
“…MIF exists not only in immune ccIls, but also in other cell types such as chicken differentiatin: cells of the eye lens, mouse 3T3 fibroblastic cells and rat Ii\ er cells . A recent report showed that MIF from the bl $vine lens has enzyme activity to catalyze the tautomerizatit m of 2-carboxy-2,3-dihydroindole-5,6-quinone (D-dopacl rome) to 5,6-dihidroxyindole-2-carboxylic acid (DHICA) [8 . Moreover, the three-dimensional structure of MIF from tb,?…”
Section: Introductionmentioning
confidence: 99%